Neurotypicals with higher autistic traits have delayed visual processing of an approaching life-sized avatar’s gait: an event-related potentials study - Inokuchi, Ryo; Ichikawa, Hiroko; Yamamoto, Masataka; Takemura, Hiroshi (Frontiers in Human Neuroscience, 2023)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder, which is reportedly related to difficulties in visual processing of human motion, such as biological motion and gestures. Moreover, neurotypical adults with higher autistic traits are clumsier than those with lower autistic traits when passing by others. We investigated the association between autistic traits in neurotypical adults and visual processing of an approaching life-sized avatar’s gait. We clarified atypical visual motion processing and autistic traits in daily life in 26 neurotypical adults by analyzing the Subthreshold Autism Trait Questionnaire (SATQ) score, a 24-item self-report scale of ASD, and event-related potentials (ERPs) in response to walking motion of a passing avatar. Videos of walking life-sized virtual avatars approaching and retreating were presented as visual stimuli. The association between the participants' scores of autistic traits and the latencies and amplitudes of the ERPs was examined. ERP components (N170 and P200) were identified in the occipito-temporal region. Thus, adults with higher autistic traits had longer latencies and lower amplitudes of P200 in the occipito-temporal region for the approaching avatar than those with lower autistic traits. These findings indicate that adults with higher autistic traits have delayed and less sensitive visual processing of the approaching avatar. It suggests that while passing another person, these individuals have atypical visual processing of their approach. This study may contribute to elucidating autistic traits from the perspective of visual processing in an environment mimicking daily life.